Pola dan Fungsi Harf Jarr dalam Kitab Dinul Islam Karya Umar bin Abdurrahman: Kajian Linguistik Arab - Muhammad Lutfi Awaludin; Akmaliyah Akmaliyah; Maman Abdul Djaliel (Dzil Majaz: Journal of Arabic Literature, 2026)
Arabic grammar studies on ḥarf al-jarr in non-Qur’anic Islamic texts used in educational contexts remain limited, despite their important role in shaping relational meaning within sentences. This study aims to analyze the grammatical functions and semantic implications of ḥarf al-jarr in the book Dinul Islam by Umar bin Abdurrahman. This research employed a qualitative descriptive approach using library research methods grounded in Arabic grammatical (nahwu) analysis. The data consisted of linguistic units containing ḥarf al-jarr collected from the entire text of Dinul Islam. Data were analyzed through classification of preposition types, examination of their functions within jar–majrūr constructions, and interpretation of contextual meanings based on syntactic relations and semantic usage. The findings show that the prepositions ‘alā, ilā, bi-, min, and fī exhibit dominant grammatical and semantic tendencies related to obligation, direction, attachment, causality, source, and contextual relations. These functions contribute not only to sentence structure but also to the formation of normative and theological meanings in the text. This study contributes to Arabic linguistic studies by providing an integrative understanding of the relationship between grammatical structure and meaning construction in non-Qur’anic Islamic discourse